Pengaruh Organizational Commitment, Human Resource Development, Dan Follower-Leader Goal Congruence Terhadap Turnover Intention Pada PT New Era Ponsel Jakarta Timur - Charles Mercelie; Netania Emilisa; Rehan Putra Dharmawan (Journal of Economics and Business UBS, 2023)
The importance of systematic human resource management for each company to be able to compete in the global market, including PT New Era Mobile and PT Ribhi Ponsel. PT New Era Mobile is a company engaged in buying and selling electronic goods by selling online and offline and serving the repair of damaged goods. While PT Ribhi Mobile is a subsidiary of the same PT New Era Mobile that conducts digital operations. This study aims to analyze the influence of Organizational Commitment, Human Resource Development, and Follower-Leader Goal Congruence on PT. New Era Mobile, as well as to evaluate the impact of Organizational Commitment and Human Resource Development on Turnover Intention in the company. The research method used is Hypothesis Testing with the aim of testing hypotheses that explain the relationship between variables, especially Organizational Commitment, Human Resource Development, and Follower-Leader Goal Congruence to Turnover Intention in PT employees. New Era Mobile Phones. Data were collected using correlational studies with a cross-sectional approach. research results, an overview of the situation of PT. New Era Mobile shows that the level of Organizational Commitment, Human Resource Development, Follower-Leader Goal Congruence, and Turnover Intention of employees tends to be positive. The results of hypothesis testing show that there is a significant negative influence between Organizational Commitment, Human Resource Development, and Follower-Leader Goal Congruence on Turnover Intention.